Organizational Adaptibility Exploration as an Intervening Variabel on the Lingkage of Trandiciplinarity and Computational Skills toward Competitiveness - Sugito, Pudjo; Gatot Sumarsono, Tanto; Kamaluddin, Kamaluddin (Business Management Research, 2022)
This reasearch intends to explore the role of organizational adaptibility as  an intervening variabel on the effect of transdiciplinarity and computational skills toward competitiveness.  The research population is small industries at the district of Malang. The number sample are 70 small scale industries. Further, this research consists of 4 constructs, 14 indicators and 3 hypothesis. All primary data are analyzed by structural equation model  with  help of AMOS program. Based on the data analysis found that transdiciplinarity and computational skills significantly indirect effect to the competitive advantage through organizational adaptability. Event, organizational adaptability significantly effect to the competitive advantage. That is due to the critical ratio value of hypotesis 1 till hypotesis 3 higher than 2.00 and also the probability value is less than 0.05.  It means that all research hypoteses are accepted. Therefore, it can be concluded that organizational adaptability mediate the effect of transdiciplinarity and computational skills to the competitiveness.